Dynamic activity of military transportation investigation at the construction site (Academic journal Industrial Machine Building Civil Engineering, 2019)
In the paper it is confirmed that any theoretical data inferior to precisely measured data due to the impossibility ofconsidering all the factors influencing on the oscillation process. The fluctuations magnitude of a non-residential building inPoltava and the dynamic influence on the building structure and the people who can be there periodically are experimentallyinvestigated. To evaluate the vibration impact, it is necessary to compare measured data with the permissible level ofvibration in public buildings. The recommendations for the further building exploitation are based on the building structuresvibration acceleration measurements results.
Keywords: vibration; building; vibration acceleration; vibration velocity; measurement